On Pointwise Approximation of Conjugate Functions by Some Hump Matrix Means of Conjugate Fourier Series. (25th May 2015) - Łenski, W.; Szal, B.
Abstract : The results generalizing some theorems onN, p n E, γ summability are shown. The same degrees of pointwise approximation as in earlier papers by weaker assumptions on considered functions and examined summability methods are obtained. From presented pointwise results, the estimation on norm approximation is derived. Some special cases as corollaries are also formulated.